Role of the halo sign in the assessment of giant cell arteritis: a systematic review and meta-analysis. Issue 3 (19th August 2021) - Sebastian, Alwin; Coath, Fiona; Innes, Sue; Jackson, Jo; van der Geest, Kornelis S M; Dasgupta, Bhaskar
Abstract: Objectives: This systematic review and meta-analysis aimed to evaluate the diagnostic value of the halo sign in the assessment of GCA. Methods: A systematic literature review was performed using MEDLINE, EMBASE and Cochrane central register databases up to August 2020. Studies informing on the sensitivity and specificity of the US halo sign for GCA (index test) were selected. Studies with a minimum of five participants were included. Study articles using clinical criteria, imaging such as PET-CT and/or temporal artery biopsy (TAB) as the reference standards were selected. Meta-analysis was conducted with a bivariate model. Results: The initial search yielded 4023 studies. Twenty-three studies (patients n = 2711) met the inclusion criteria. Prospective (11 studies) and retrospective (12 studies) studies in academic and non-academic centres were included. Using clinical diagnosis as the standard (18 studies) yielded a pooled sensitivity of 67% (95% CI: 51, 80) and a specificity of 95% (95% CI: 89, 98%). This gave a positive and negative likelihood ratio for the diagnosis of GCA of 14.2 (95% CI: 5.7, 35.5) and 0.375 (95% CI: 0.22, 0.54), respectively. Using TAB as the standard (15 studies) yielded a pooled sensitivity of 63% (95% CI: 50, 75) and a specificity of 90% (95% CI: 81, 95). Conclusion: The US halo sign is a sensitive and specific approach for GCA assessment and plays a pivotal role in diagnosis of GCA in routine clinical practice. Registration: PROSPERO 2020 CRD42020202179.